Metode Penilaian Harga Call Option Atas Warant Perbankan Di Indonesia Menggunakan Metode Penilaian Harga Call Option Dibandingkan Dengan Harga Pasar - Budi Lesmana; widiawati, santi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
The purpose of this research is to know the application from the valuation method of the call option price for the warrant of the banking sector in the Indonesian Stock Exchange, after that the theoretical price from the valuation method of the call option price could be compare with the market price. The research conducted with four warrants of the banking sector that have quite active transactions, there are BNII-W, BNII-W2, BNLI-W, and PNBN-W. The research begin with the calculation of the risk from the stock as the underlying asset for the warrant. Then continued with the recognition for other indicators that need to calculate the theoretical price of the call option price with the Black-Scholes Option Pricing Model, there are stock price, exercise price, risk free interest rate (SBI), and remaining time of the warrant from the exercise date. Theoretical price with the Black-Scholes Option Pricing Model could be compare with the market price of the warrant. Then could be known the comparison of the movement between theoretical price with the market price. From the result of the research showed that the market price is different with the theoretical price with the Black-Scholes Option Pricing Model for BNII-W, BNII-W2, BNLI-W, and PNBN-W. The difference for BNII-W2 is not statistically significant, while the difference for BNII-W, BNLI-W, and PNBN-W are statistically significant. The movement of the market price for BNII-W, BNII-W2, BNLI-W, and PNBN-W are not always move to the new theoretical equilibrium price with the Black-Scholes Option Pricing Model. The difference in the value and the movement between market price with the theoretical price could be caused by the condition of the Indonesian capital market that is not in the efficient condition yet, this could be indicated that the transaction have not reflect for full information. Besides that the option instrument is still not completely traded in the Indonesian Stock Exchange, so the investor could not used the difference between the market price and the theoretical price with some arbitrage to get gain.